The nature of creativity The roles of genetic factors, personality traits, cognitive abilities, and environmental sources. [article]. - Kandler, Christian
This multitrait multimethod twin study examined the structure and sources of individual differences in creativity. According to different theoretical and metrological perspectives, as well as suggestions based on previous research, we expected 2 aspects of individual differences, which can be described as perceived creativity and creative test performance. We hypothesized that perceived creativity, reflecting typical creative thinking and behavior, should be linked to specific personality traits, whereas test creativity, reflecting maximum task-related creative performance, should show specific associations with cognitive abilities. Moreover, we tested whether genetic variance in intelligence and personality traits account for the genetic component of creativity. Multiple-rater and multimethod data (self- and peer reports, observer ratings, and test scores) from 2 German twin studies-the Bielefeld Longitudinal Study of Adult Twins and the German Observational Study of Adult Twins-were analyzed. Confirmatory factor analyses yielded the expected 2 correlated aspects of creativity. Perceived creativity showed links to openness to experience and extraversion, whereas tested figural creativity was associated with intelligence and also with openness. Multivariate behavioral genetic analyses indicated that the heritability of tested figural creativity could be accounted for by the genetic component of intelligence and openness, whereas a substantial genetic component in perceived creativity could not be explained. A primary source of individual differences in creativity was due to environmental influences, even after controlling for random error and method variance. The findings are discussed in terms of the multifaceted nature and construct validity of creativity as an individual characteristic. -- (from the authors)
Keywords: Rieman, Rainer; Perceived creativity; Tested figural creativity; Personality; Intelligence; Multitrait multimethod twin study